The construction process of teaching professionals: aspects concerning issues initial training - Souza, Nathália Cristina Amorim Tamaio de; Passalacqua, Flávia Graziela Moreira (Universidade Estadual de Campinas, 2019)
This paper was written from experiences and records collected during teaching activities taught to two classes of the fourth year of the Pedagogy course of a university in the interior of São Paulo. Its main objective is to provoke reflections on the aspects of teacher professionalism that are developed or should be developed in the context of initial teacher training. For that, a qualitative study of an empirical nature was carried out, which counted on the appreciation of fifty written productions of licensees, analyzed according to the technique of Content Analysis and collated with the area reference. These productions were guided by questions that problematized the place of the initial formation in the process of constitution of the teaching professional, what can be anticipated on the teaching activity before the effective professional entrance and what are the elements capable of preparing the future teacher for a safe career start. The results of the study showed that the graduates demand a training that articulates more clearly the theory and the practice and that prepares them better in didactic and behavioral aspects for the insertion to the teaching.